Preparing high-quality vanadium titano-magnetite pellets for large-scale blast furnaces as ironmaking burden. (7th February 2020) - Gan, M.; Sun, Y.-F.; Fan, X.-H.; Ji, Z.-Y.; Lv, W.; Chen, X.-L.; Jiang, T.
ABSTRACT: The oxidation behaviour and the phase and microstructure evolution of VTM (vanadium titano-magnetite) pellets were studied during thermal processing in order to optimise the production method for producing high-quality pellets. The oxidation tests showed that titanium magnetite and ilmenite in VTM began to oxidise at 500°C and 700°C, respectively. When the temperature reached 875°C, VTM was mainly oxidised to Fe2 O3, while Fe2 TiO5 was the main oxidation product when the temperature reached 1050°C. The consolidation of the pellets was affected by the degree of oxidation and the oxidation products. Results indicated that the most suitable oxidation ratio was about 70%, and the preferred mineral phase was recrystallised Fe2 O3, which was beneficial to improving pellet consolidation in roasting process. The most appropriate oxidation condition was 875°C for 12 min, which contributed to forming more Fe2 O3 phase, and the compressive strength of roasted pellet reached 2939 N. The pellets could be used as a high quality ironmaking burden for large-scale blast furnaces.